The Development of Competency Enhancing Based on Buddhist Psychology for Engineering Personnel - Semawonganun, Sinchai; Phoowachanathipong, Kamalas; Buasiri, Amnaj (Journal of International Buddhist Studies, 2019)
This mixed method research aimed to study the results of self-development based on Buddhist psychology principles to enhance the competency of engineering personnel. The 64 samples, using the G * Power were divided into 32 people in experimental groups and 32 people in control groups. The research tools were the competency measurement, behavior observation and self-development program. The experimental training was divided into phase I for 3 days, 2 nights, phase II for 1 month and follow-up period for 1 month. Research data were analyzed by T-test, Two-way repeated measures ANOVA and content analysis. The research found that he competency enhancing program consisted of 14 activities and IOC of the program was between 0.875 –1. The program is suitable and effective for reduction to practice. The comparison of the average scores of the competencies shown that the engineering personnel competencies after the experiment were higher than before the experiment and higher than the control group with statistical significance at the level of .05